Surgical Resection of a Ruptured Pancreaticoduodenal Artery Aneurysm - Takei, Tomohide (Am J Case Rep, 2016)
Patient: Female, 71 Final Diagnosis: Rupture of a pancreaticoduodenal artery aneurysm Symptoms: — Medication: — Clinical Procedure: Surgical operation Specialty: Surgery OBJECTIVE: Rare disease BACKGROUND: Ruptured aneurysms of the pancreaticoduodenal artery result in fatal hemorrhage and high mortality. Therefore, prompt diagnosis and treatment are required, but there are sometimes problems differentiating this specific diagnosis from other abdominal pathologies. CASE REPORT: We encountered a rare case of a ruptured pancreaticoduodenal artery aneurysm with an atypical clinical presentation that simulated acute pancreatitis. A 71-year-old woman was admitted to the emergency department with abdominal pain in the left upper quadrant, a slightly elevated level of pancreatic amylase, and cholelithiasis on ultrasonography. With persistent pain and progressively decreasing hemoglobin level, computed tomography with contrast showed fluid collection in the subphrenic space, a retroperitoneal hematoma, and a pancreaticoduodenal artery aneurysm that appeared to originate from a branch of the SMA. Urgent angiography indicated spontaneous rupture of a pancreaticoduodenal artery aneurysm. Emergent surgery was undertaken, and a simple aneurysmectomy was successfully performed. The patient’s recovery was unremarkable. The prompt diagnosis of a pancreaticoduodenal artery aneurysm was difficult because the initial symptoms were vague and misleading in our case. CONCLUSIONS: A high level of suspicion, rapid diagnostic capability, and prompt surgical or endovascular intervention, as well as effective teamwork in the emergency department, are critical to avoid the devastating consequences of a ruptured visceral artery aneurysm.